The novel life of Jane Austen : a graphic biography - Barchas, Janine (Black Dog, & Leventhal Publishers, 2025)
"Combining deep scholarship and serious whimsy, The Novel Life ofJane Austen presents this literary icon as the starring character in her own graphic novel. Told in three parts (Budding Writer, 1796-1797); Struggling Artist, 1801-1809; Published Author, 1811-1817), the gritty circumstances of Austen's own genteel poverty and the smalldaily injustices so often borne by creative women at this time are told against the backdrop of Georgian England and reflect, down to the smallest detail, many of the plots and characters woven into Austen's greatest works. All the settings and scenarios presented here are based upon the historical record, including the clothing, architecture, decor, and Regency locations. Sprinkled throughout, the Easter eggs and clever references to popular film adaptations of Austen's novels will satisfy the casual and avid Austen fan alike"--